Given the function
![y=(2)/(x^2)+9](https://img.qammunity.org/2023/formulas/mathematics/college/1b8su9gml0k044vvyhiv181qfmrgae24sl.png)
since y=(f(g(x))
We need to find f(x) and g(x)
f(x) is
![f(x)=x+9](https://img.qammunity.org/2023/formulas/mathematics/college/j9d9r5k99j12fbffhd1fp6rarpxvgk5xnn.png)
then
g(x)
![g(x)=(2)/(x^2)](https://img.qammunity.org/2023/formulas/mathematics/college/z220tfogtu1wkznbgcmzaliwdmqnqyyvf7.png)
then
![y=f(g(x))=(2)/(x^2)+9](https://img.qammunity.org/2023/formulas/mathematics/college/c0jmbz6ennwjb9sonhow6llhg0fc9s71wx.png)
We have
![y=(2)/(x^2)+9](https://img.qammunity.org/2023/formulas/mathematics/college/1b8su9gml0k044vvyhiv181qfmrgae24sl.png)
replace then
![(2)/(x^2)=X](https://img.qammunity.org/2023/formulas/mathematics/college/ei49eo7nl99la4iw1pplrf6aslgf7c836t.png)
now we have
![y=X+9](https://img.qammunity.org/2023/formulas/mathematics/college/a1s30et0wob0x6zgw6rsrnmysuzc2zqi3j.png)
now we are give that
y=(f(g(x))
this means that for a function f(x) the value of x is replace with the function g(x)
then the only option to complete this statement is that
f(x)=X+9
but remember X=